Strategic Equilibrium: Merging Optimization and Sustainability in B2B Supply Chains - Vijayendra Vittal Rao (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As global trade changes, B2B supply chains are under more and more pressure to be both environmentally friendly and run well. This study looks at the idea of strategic equilibrium, which is when optimization goals like cutting costs, shortening lead times, and making sure services are reliable are balanced with sustainability goals like lowering carbon footprints, using less energy, and making less waste. Employing a mixed-methods research strategy, the study blends quantitative performance analysis with qualitative insights from industry experts. We created a Strategic Equilibrium Index (SEI) to measure how well optimization and sustainability strategies are working together in certain companies. The results show that companies with higher SEI scores likely to do better in terms of operational performance, customer satisfaction, and environmental stewardship. The study shows that when sustainable supply chain strategies are strategically matched with performance optimization, they produce long-term value, resilience, and a competitive edge in B2B ecosystems.